A novel bio-based epoxy resin from oligomer: Excellent processability, high heat resistance, and intrinsic flame retardancy - S. H. Liu; X. Q. Zhang; J. H. Liu; C. H. Lei; Z. X. Dong (eXPRESS Polymer Letters, 2021)
Preparing an epoxy resin with biomass resources as an alternative for bisphenol A is significant for sustainable and renewable development under great pressure of limited fossil resources and urgent environmental issues. Herein, we synthesized an epoxy oligomer P-DBP-EP-n derived from biomass magnolol through an efficient one-step glycidylation. P-DBP-EP-n exhibited a low viscosity of 11.7 Pa・s at room temperature, endowing it with excellent processability as diglycidyl ether of bisphenol A (DGEBA) and magnolol-based epoxy monomer EDBP. Then P-DBP-EP-n was cured with a diamine curing agent, 4,4′-diaminodiphenyl methane (DDM), and following thermal addition polymerization of allyl units. Compared with DGEBA/DDM and EDBP/DDM, P-DBP-EP-n/DDM possessed a higher glass transition temperature (Tg) (304 to 167 and 226 °C), implying distinguished heat resistance. Furthermore, the tensile properties and notched impacted strength of P-DBP-EP-n/DDM were better than EDBP/DDM (20.7 to 19.4 MPa, 2.0 to 1.6 GPa, and 2.5 to 2.0 kJ/m2). The initial degradation temperature and char residue of P-DBP-EP-n/DDM were 421 °C and 35.2%, with a 13.5 and 101% increase compared with those of DGEBA/DDM, respectively. Additionally, P-DBP-EP-n/DDM displayed outstanding flame retardancy with V-0 rate for the vertical burning test and limiting oxygen index value of 47.7%, which was almost twice as much as that of DGEBA/DDM. This study offers a promising and feasible pathway to obtain a fully bio-based epoxy resin substituted for petroleum-based DGEBA with distinguished processability, heat resistance, and flame retardancy. Comprehensive properties of the bio-based thermosets are expected to be further regulated by the thermal addition polymerization of allyl units.